Oxford SWIFT integral field spectrograph and multiwavelength observations of the Eagle galaxy at z=0.77 - Kassin, SA; Fogarty, L; Goodsall, T; Clarke, F; Houghton, R; Salter, G; Thatte, N; Tecza, M; Davies, R; Weiner, B; Willmer, C; Salim, S; et al. (2011)
The 'Eagle' galaxy at a redshift of 0.77 is studied with the Oxford Short Wavelength Integral Field Spectrograph (SWIFT) and multiwavelength data from the All-wavelength Extended Groth strip International Survey (AEGIS). It was chosen from AEGIS because of the bright and extended emission in its slit spectrum. 3D kinematic maps of the Eagle reveal a gradient in velocity dispersion which spans 35-75 ± 10kms-1 and a rotation velocity of 25 ± 5kms-1 uncorrected for inclination. Hubble Space Telescope images suggest it is close to face-on. In comparison with galaxies from AEGIS at similar redshifts, the Eagle is extremely bright and blue in the rest-frame optical, highly star forming, dominated by unobscured star formation and has a low metallicity for its size. This is consistent with its selection. The Eagle is likely undergoing a major merger and is caught in the early stage of a starburst when it has not yet experienced metal enrichment or formed the mass of dust typically found in star-forming galaxies. © 2011 The Authors Monthly Notices of the Royal Astronomical Society © 2011 RAS.